PENGARUH KINERJA KEUANGAN DAERAH, TINGKAT PARTISIPASI ANGKATAN KERJA, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Aisyah Syafitri; Ariusni Ariusni (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine the effect of regional financial performance, labor force participation rates, and inflation on economic growth in West Sumatra. The data used are secondary data in the form of time series with a period of time from 1987 to 2017, with the technique of collecting data documentation and library studies obtained from the institutions and agencies concerned. The variables used are government expenditure, investment, balance funds, labor force participation rates, inflation and economic growth. The research methods used are: (1) Ordinanry Least Square (OLS), (2) Classical Assumption Test. The results of the study show that (1) Government expenditure has a positive and significant effect on economic growth. (2) FDI investment has a negative and not significant effect on economic growth. (3) Balancing Funds have a positive and significant effect on economic growth. (4) Work Force Participation Level has a negative and significant effect on economic growth. (5) Inflation has a negative and significant effect on economic growth (6) Government Expenditures, Investment, Balancing Funds, Labor Force Participation Levels and Inflation have a significant effect on economic growth in West Sumatra.